Post-translational Modification Regulates Formation and Cargo-Loading of Extracellular Vesicles - Carnino, Jonathan M.; Ni, Kareemah; Jin, Yang (Frontiers in Immunology, 2020)
Accumulating evidence suggests that post-translational modifications (PTMs) regulate the selective encapsulation of non-coding RNA molecules into extracellular vesicles (EVs) and contribute to the downstream functions of EVs or EV-cargo non-coding RNAs. EVs represent a novel mechanism of intercellular communication that involves the transfer of molecules, including but not limited to proteins, lipids, and non-coding RNAs, to induce functional changes in the recipient cells. In this present mini-review, we focus on the PTM-regulated protein and non-coding RNA selection into eukaryotic EVs.